Analisis Gaya Bahasa dan Nilai Pendidikan Karakter Film Jagat Raya Karya Andri Sofyansyah - Lyly C. Aprianty Hutauruk; Marlina Agkris Tambunan; Monalisa Frince Sianturi; Martua Reynhat Sitanggang Gusar (Medan Resource Center, 2021)
This study aims to describe the most dominant language style and character education values used in Andri Sofyansyah’s film universe. This type of research uses a qualitative descriptive method, namely, describes the language style and character education values used. Dominant in the film universe. The data collection method in this study is the listening method, using the basic data collection technique used is the tapping technique. The results of the analysis of the characteristics of language style and the value of character education in Andri Sofyansyah’s universe film (1) find the dominant language style in Andri’s universe film Sofyansyah (2) looking for the dominant character education values in Andri Sofyansya’s universe film universe.